Corporate governance, chief executive officer power and performance of Islamic banking in east africa - Karama , Fauziya Brek (Eastern Journal of Economics and Finance, 2023)
This study aims to investigate the relationship between corporate governance variables, CEO power, and the performance of Islamic banking in East Africa. A Hierarchical panel regression model was to test both direct and indirect effect. Panel data was collected from all 10 full-fledged Islamic banking in East Africa and conventional banks with Islamic banking window for 7 years (2013-2020). Empirical results showed that board independence, board financial expertise and board activity positively affect performance of Islamic banking in East Africa. Powerful CEO negatively moderated the effect of board independence and board financial expertise on performance of Islamic banking in East Africa. Based on the findings, board independence, board financial expertise and board activity play a major role on improving performance of Islamic banking. In addition, the study support agency theory perspective that powerful CEO can reduce independence of board directors, hence limiting board activity and board financial expertise positive contribution on performance of Islamic banking. There has been limited studies on corporate governance and performance of Islamic banking in East Africa. This study contributes on board independence, board financial expertise and board activity of Islamic banking literature. The study provided crucial insight on corporate governance variables of Islamic banking in East Africa and their link performance.